A Quantitative Study on The Relationship Between Student Engagement and English Achievement - Jabal Shofan Shofa; Mauly Hikmat; Abdillah Nugroho (Jurnal Pendidikan Bahasa Inggris Undiksha, 2026)
Students’ engagement in class, play a pivotal role in shaping their academic performance and believed to be the main contributor to immediate and future academic achievement. Thus, this study aim to explore whether students’ engagement in English class has a significant impact on their English achievement. The researcher used quantitative research with survey-based technique. The researcher used purposive sampling by choosing 9th grade. It involved  47 students, devide into two classes. 24 students in 9A are male students and 23 students in 9B are female students, all enrolled in  Muhammadiyah Daarul Arqom Junior High School in academic year 2024/2025. The researcher use Student Engagement Instrument (SEI) from the University of Minnesota to measure students’s engagement level in classroom. And  collected students English achievement from their Report card. The result from this research is statistically analyzed using IBM SPSS Statistics 25 with Pearson correlation test, showing the r-obtained of 9A students is 0.884 and 9B students is 0.917, were higher than r-table 0.515 for 24 subjects and 0.526 for 23 subjects. Which mean, there is a strong correlation between students’ engagement level in English class and students’ English achievement. Further discussion will be explained in this study